The use of acid whey for the production of yogurt-type fermented beverages - Katarzyna Skryplonek (Mljekarstvo, 2018)
Acid whey is a by-product of cheese-making industry, which, in comparison to rennet whey, has less favourable processing properties and thus it is more difficult to utilize. The aim of the study was to evaluate the quality of yogurt-type fermented beverages based on acid whey. In the beverages production yogurt bacteria cultures Streptococcus thermophilus and Lactobacillus delbruecki ssp. bulgaricus (YO-MIX, Danisco, Denmark) were used. The production process included combining of pasteurized acid whey with UHT milk, unsweetened condensed milk or skimmed milk powder. Milk was incorporated to beverages in order to enrich casein content and obtain product with quality characteristics similar to fermented milk drinks. Moreover, the beverages were supplemented with oligofructose and whey protein concentrate WPC 35. The products were stored under refrigerated conditions (5±1°C) for 21 days. During the storage, an assessment of physicochemical properties and sensory characteristics was carried out. In addition, the beverages were evaluated in consumer preference test. The study showed, that by combining of acid whey with milk it is possible to obtain a products similar to yogurt, although their characteristics were influenced by the composition and storage time. During storage period, the acidity increased and acetaldehyde content decreased. Moreover the deterioration of sensory properties was observed. Consumer preference test indicated, that the best sensory properties had beverages from whey and condensed milk.